85 Adapting education to support generation Z student nurses in a pandemic. (15th December 2021) - Hudson, Natalie; Tonkin, Tabitha; Phelan, Amy; Fitz-Costa, Natalie; Khan, Moeen; Sasu, Deborah; Porter, Lauren
Abstract : Rationale: With increasing numbers of Generation Z nurses in the workforce and the majority of our undergraduate nurse's consisting of Gen Z, it is vital that we are responsive to their needs, and more so during the pandemic due to the large amount of disruption to their learning. As an Undergraduate team, we responded and adapted our education and pastoral support throughout, to meet the needs of Generation Z. Description: Since March 2020 student nurses were greatly impacted by the pandemic. They had reduced or cancelled clinical placements and no university face to face contact. Furthermore, the lack of contact and added anxieties hugely impacted on their mental health and wellbeing. In response and in line with the needs of Generation Z, we responded with weekly virtual teaching and wellbeing support sessions. Social media platform was introduced to ensure current and effective communication and 'Lightening learning' sessions were rolled out meeting the generation's need for short, concise teaching. Results: Since March 2020 we have adapted to maintain student placements at GOSH, with a total of 4128 placement weeks from March 2020- March 2021, whilst maintaining high placement standards with evaluation data showing an overall average of 4.6 out of 5.0 scored. The introduction of a social media account proved successful, with over 70% of our regular university's students now accessing the platform and has resulted in, all teaching and student forums getting fully booked. Roaming lightening teaching commenced, with an average of 5 sessions delivered on the wards per week, allowing students to remain in their ward areas whilst continuing to receive the education and support they required. Wellbeing socially distanced walks were introduced to provide face to face essential support, as well as virtual weekly catch ups during the first wave, with a total of 16 sessions delivered.